The effects of corticotropin-releasing factor (CRF) and urocortins on the noradrenaline (NA) released from the locus coeruleus (LC) - Táncsics Patrícia (PEPTIDES, 2024)
Corticotropin-releasing factor (CRF) activates the hypothalamic-pituitary-adrenal (HPA) axis and stimulates the noradrenergic neurotransmission, both processes being implicated in the pathogenesis of anxiety and depression, but the intimate site and mechanism of interaction of CRF and CRF-related peptides, named urocortins (UCN1, UCN2, UCN3), with noradrenaline (NA) was not fully elucidated yet. Therefore, the aim of the present study was to investigate the actions of CRF and urocortins on the NA released from the rat locus coeruleus (LC), the primary source of NA in the brain, and the participation of CRF receptors (CRF1 and CRF2) in these actions. In order to do so, male Wistar rats were used, their LC were isolated and dissected, and the LC slices were incubated with tritium-labelled NA, superfused and stimulated electrically. During superfusion, the LC slices were treated with CRF, UCN1, UCN2 or UCN3, and, when significant effect was observed, pretreated with selective CRF1 antagonist antalarmin or selective CRF2 antagonist astressin2B. The release of tritium-labelled NA from the LC was determined by liquid scintillation counting. CRF and UCN1 increased significantly the tritium-labelled NA release from the LC, and these effects were reduced by antalarmin, but not by astressin2B. In addition, UCN2, but not UCN3, decreased significantly the tritium-labelled NA release from the LC, and this effect was reversed by astressin2B, but not antalarmin. Our results indicate the existence of two apparently opposing CRF systems in the LC, since activation of CRF1 by CRF and UCN1 stimulated, whereas activation of CRF2 by UCN2 inhibited the NA release. © 2024